If you only knew - Vail, Rachel (New York Scholastic, 1998)
Seventh-grader Zoe, who comes from a big family where she's never had anything all to herself, desperately wants CJ for a best friend, but when CJ reveals that she likes the boy Zoe likes, she must make a choice.
Keywords: Friendship -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; Family life -- Fiction